2015
DOI: 10.1007/s13277-015-4252-y
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of lncRNA-ATB correlates with clinical progression and unfavorable prognosis in pancreatic cancer

Abstract: Long noncoding RNAs (lncRNAs) have been shown to play critical roles in the development and progression of diseases. lncRNA activated by transforming growth factor beta (TGF-β) (lncRNA-ATB) was discovered as a prognostic factor in hepatocellular carcinoma, gastric cancer, and colorectal cancer. However, little is known about the role of lncRNA-ATB in pancreatic cancer. This study aimed to assess lncRNA-ATB expression in pancreatic cancer and explore its role in pancreatic cancer pathogenesis. Quantitative real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…This was validated in our current study, in which elevated lnc-ATB expression was positively correlated with ESCC carcinogenesis. However, Qu et al 18 reported that expression of lnc-ATB decreased in pancreatic cancer tissues and cell lines, and decreased lnc-ATB expression was an independent predictor of poor prognosis in pancreatic cancer patients. Overall, these data suggest that there is a cancer specific expression pattern of lnc-ATB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was validated in our current study, in which elevated lnc-ATB expression was positively correlated with ESCC carcinogenesis. However, Qu et al 18 reported that expression of lnc-ATB decreased in pancreatic cancer tissues and cell lines, and decreased lnc-ATB expression was an independent predictor of poor prognosis in pancreatic cancer patients. Overall, these data suggest that there is a cancer specific expression pattern of lnc-ATB.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, lnc-ATB could promote trastuzumab resistance and the invasion-metastasis cascade in breast cancer by competitively binding miR-200c and upregulating ZEB1 and ZNF-217, resulting in EMT. 13 Dysregulation of lnc-ATB have been reported in human tumors including gastric, 14 colorectal, 15, 16 brain, 17 pancreatic 18 and renal 19 cancer. However, expression of lnc-ATB in ESCC and the underlying mechanisms remain unsolved.…”
mentioning
confidence: 99%
“…However, in contrast to the above findings in other malignancies, lncRNA-ATB was found to be downregulated in pancreatic cancer, with low levels being associated with advanced and metastatic disease [293]. Likewise, miR-200a and miR-200b, have been shown to be overexpressed in pancreatic cancer despite being downregulated in many other cancers [294].…”
Section: Lncrnas and Emt: The Main Playersmentioning
confidence: 99%
“…Qu et al reported that lncRNA-ATB was directly correlated with clinical endpoints (overall survival) and could serve as an independent prognosis maker for pancreatic cancer patients [15]. Saito et al showed that increased lncRNA-ATB expression was a significant prognostic for increased recurrence and decreased survival of GC patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high expression of lncRNA-ATB participated in the development of colorectal cancer (CRC) and was a novel indicator of poor prognosis in patients with CRC [14]. Low expression of lncRNA-ATB plays a critical role in pancreatic cancer progression and prognosis, and may serve as a potential prognostic biomarker in pancreatic cancer patients [15]. However, the study investigated the role of lncRNAs in CWP is limited.…”
Section: Introductionmentioning
confidence: 99%